The theatre student: Gilbert and Sullivan production - Kline, Peter (New York, Rosen Press, 1972)
Describes the plot and characters of the Gilbert and Sullivan operet tas and discusses staging, casting, and other aspects of production for an amateur company.
Bibliography: p. 295-299.
Keywords: Gilbert, W. S. -- 1836-1911.; Sullivan, Arthur, -- 1842-1900.; Gilbert, W. S. -- 1836-1911.; Sullivan, Arthur, -- 1842-1900.; Operetta; Amateur theater; Operetta; Amateur theater